Effectiveness of Galega Officinalis Mother Tincture as an Anti Diabetic in Type 2 Diabetes Mellitus (Advancements in Homeopathic Research, 2023)
Diabetes mellitus is considered as the most important  public health threat which has affected millions of  people around the globe of all gender, ages, ethnic  groups and race. Homoeopathy being a system  of holistic approach, there are remedies based on  the individualizing characteristic symptoms. In  homoeopathic system Galega officinalis mother  tincture is one among the antihyperglycemic  medicine. Aqueous and ethanolic extract of Galega  officinalis showed a hypoglycaemic effect in our  research study. Thirty clinically diagnosed cases  of T2DM were taken for the study. Most of the  patients have got relief both symptomatically and  diagnostically Hence, this study shows that Galega  officinalis mother tincture is effective in treating type  II Diabetes mellitus [1].
Keywords: Type 2 Diabetes mellitus; Galega officinalis; Anti-diabetiC; Mother tincture